2019
DOI: 10.1177/1526924819853836
|View full text |Cite
|
Sign up to set email alerts
|

The Patients Save Lives Program to Facilitate Organ Donor Designation in Primary Care Offices

Abstract: Background: There are about 120 000 people on the US waiting list for a solid organ transplant; nearly 22 people die every day who could be helped through organ donation. Joining a donor registry and informing one’s family of one’s preferences increases recovery rates and can avoid misunderstandings during an emotionally difficult time. Although the vast majority of people support organ donation, only about half of adults have joined a state donor registry. Methods. A 3-group design was used. Primary care phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In a recent trial based in primary care, Degenholtz and colleagues used a standard two-arm trial design where the intervention arm involved primary care staff providing a physical (paper) donor designation form directly to patients to fill out [ 8 ]. They showed that 761 (8.1%) of the 9428 people who were not already registered completed the designation form to be organ donors and none in the comparatively smaller control group who were not directly provided with a form registered (0%; 0/579).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent trial based in primary care, Degenholtz and colleagues used a standard two-arm trial design where the intervention arm involved primary care staff providing a physical (paper) donor designation form directly to patients to fill out [ 8 ]. They showed that 761 (8.1%) of the 9428 people who were not already registered completed the designation form to be organ donors and none in the comparatively smaller control group who were not directly provided with a form registered (0%; 0/579).…”
Section: Discussionmentioning
confidence: 99%
“…Family physician offices are a promising—yet under-investigated—setting for promoting organ donation registration [ 7 , 8 ]. Family physicians are a trusted source of health information and most Canadians see their family doctor at least once a year.…”
Section: Introductionmentioning
confidence: 99%
“…But, as they are not practicing it so these programs should be conducted at national level also. [3839]…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies showed that healthcare professionals with positive attitudes towards organ donation are more likely to begin the organ donation process by seeking and obtaining consent from potential donor families 8. Recently, some reviews demonstrated that primary care interventions, for example, delivering organ donation information during practices and annual health check by trained general practitioners and staff, can significantly improve the organ donation registration rates,9 with more similar models were under trial 10 11. These indicated that doctors would play a more active role in organ donation promotion in the future, and they should be more prepared for it.…”
Section: Introductionmentioning
confidence: 99%